Melanocytic Lesions of the Nail Unit - Pembegül Güneş; Fatih Göktay (MDPI AG, 2018)
Melanocytic lesions of the nail unit are traditionally classified as follows: melanocytic activation, lentigo, nevi, and melanoma. Undoubtedly, melanoma is the most important malignant tumor of the nail unit. Differentiating nail unit melanoma from other melanocytic lesions is often difficult both clinically and histopathologically. This article will first describe the histology of the nail unit, followed by a brief summary of clinical and histopathological features as well as differential diagnosis of melanocytic lesions of the nail unit.